ANALYSIS OF THE EFFECTIVENESS OF THE IMPLEMENTATION OF DIGITALIZATION IN OFFICE ADMINISTRATION AT PT SAKA FARMA LABORATORIES DEPOK BRANCH - Tsamara Salsabila; Christian Wiradendi Wolor; Eka Dewi Utari (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
The development of digital technology has led to very significant changes in various fields, including in the world of office administration. The application of digitalization in office administration has a major impact on work effectiveness and productivity. The purpose of this study is to analyze the effectiveness of the application of digitalization in office administration, identify the challenges faced and solutions, and find the benefits arising from its application. This research method uses a descriptive qualitative research approach. The results showed that the implementation of digitalization at PT Saka Farma Laboratories Depok Branch has increased the effectiveness of work and productivity of the company even though there are several challenges such as network disruptions, technical problems in applications, and the need for training in adapting new technology for senior employees, but from these challenges the solutions provided can be in the form of special training, implementing a data backup system, strengthening internal networks, and increasing coordination between the center and branches. The benefits of digitalization have provided convenience and a positive work spirit to continue to develop following the changing times that are increasingly complex.